Single‐cell RNA sequencing reveals the characteristics of cerebrospinal fluid tumour environment in breast cancer and lung cancer leptomeningeal metastases. Issue 6 (9th June 2022) - Ruan, Haoyu; Wang, Zhe; Sun, Ziwei; Wei, Jia; Zhang, Lei; Ju, Huanyu; Wang, Ting; Zhang, Chao; Guan, Ming; Pan, Shiyang
Abstract: Leptomeningeal metastases (LM) occur in patients with breast cancer (BC) and lung cancer (LC) showing exceptionally poor prognosis. The cerebrospinal fluid (CSF) tumour microenvironment (TME) of LM patients is not well defined at a single‐cell level. Based on the 10× genomics single‐cell RNA sequencing (scRNA‐seq) data from GEO database including five patient‐derived CSF samples of BC‐LM and LC‐LM, and four patient‐derived CSF samples of idiopathic intracranial hypertension (IIH) as controls, we analysed single‐cell transcriptome characteristics of CSF TME in LM patients compared to controls simultaneously and comprehensively. In addition, we performed 10× genomics scRNA‐seq on CSF cells derived from a BC‐LM patient to help generate a solid conclusion. The CSF macrophages in LM patients showing M2‐subtype signature and the emergence of regulatory T cells in LM confirmed the direction of tumour immunity toward immunosuppression. Then, the characteristics of CSF circulating tumour cells (CTCs) of breast cancer LM (BC‐LM) patients were classified into five molecular subtypes by PAM50 model. The communication between macrophages and five subtype‐specific CSF‐CTCs showed largest number of ligand‐receptor interactions. The five subtypes‐specific CSF‐CTCs showed great heterogeneities which were manifested in cell proliferation and cancer‐testis antigens expression. Gene regulatory networks (GRNs) analysis revealed that transcription factor SREBF2 was universally activated in the five subtypes‐specific CSF‐CTCs. Our results will provide inspiration on new directions of the mechanism research, diagnosis and therapy of LM. Abstract : Integrated analysis of characteristics of CSF tumour environment of LM patients. Five subtype‐specific CSF‐CTCs of breast cancer showed great heterogeneities on cell proliferation and cancer‐testis antigens expression. Gene regulatory networks (GRNs) highlighted transcription factor SREBF2 activated in the breast cancer CSF‐CTCs